KOLABORASI INTEGRATED MARKETING COMMUNICATION PT. MAHIRAH MUAMALAH SYARIAH DALAM MENUNJANG USAHA MIKRO KECIL MENENGAH - Deni Yanuar; Hana Azmi; Sari Rahmani; Rahmat Saleh; Novi Susilawati (SOURCE : Jurnal Ilmu Komunikasi, 2023)
The City of Banda Aceh Government established PT Mahirah Muamalah Syariah as a form of attention to SME actors. The phenomenon studied is about how PT MMS employees promote through IMC to attract SME actors to become customersThis type of research uses a descriptive method with a qualitative approach, which is carried out by presenting descriptive and detailed data about a phenomenon that occurs. The data collection method used consisted of interviews with 3 informants and also documentation aimed at strengthening the data obtained. Sources of data obtained in two ways, namely through primary data and secondary data. From the five components or indicators of IMC implemented by PT MMS, it is clear that the party from PT MMS has implemented this method based on the rhetorical theory of invitation that the researcher uses. It can be seen in how they convey persuasive information to attract SME actors in The City of Banda Aceh as customers of PT MMS. In the program carried out by PT MMS for SME actors in The City of Banda Aceh, it is quite successful, this can be seen in each of the IMC indicators they use. The facts on the ground show that PT MMS is a microfinance institution that really helps SME actors in The City of Banda Aceh through the IMC strategy they use and the responses from informants involved in the research process.